ANALISIS ANGGARAN KAS SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN PADA TOKO PHALENG COLLECTION & CUSTOM - Ahmad Tomu; Felisia Angreyani (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2021)
This research aims to determine the effect of the cash budget as a tool for planning and controlling the level of effectiveness and efficiency at the Phaleng Collection & Custom Store for the period 2019-2020. The research method used is descriptive qualitative. The analysis begins by collecting data from the Phaleng Collection & Custom Store, then analyzing how to use the cash budget and then making a comparison between theory and practice in the field. The results of this research, it is known that the cash budget as a planning and controlling tool has an influence on the level of effectiveness and efficiency